2020
DOI: 10.1186/s12885-020-06791-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of LGR5 expression in poorly differentiated colorectal carcinoma with mismatch repair protein deficiency

Abstract: Background: Leucine-rich repeat-containing G-protein-coupled receptor 5 (LGR5) is a promising intestinal stem cell and carcinoma stem cell marker. We examined the relationship between mismatch repair (MMR) protein deficiency and LGR5 expression in poorly differentiated (PD) colorectal carcinoma (CRC). Methods: In 29 cases of PD-CRC, deficiencies in MMR proteins (MLH1, PMS2, MSH2, MSH6) and β-catenin expression were identified by immunohistochemistry (IHC).LGR5 expression was examined by the RNAscope assay in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…We first aimed to determine cell type composition differences between MSI-H and MSS/MSI-L CRC tumors. We replicated a number of known findings, including increased CD8 + T cells and macrophages in MSI-H tumors, which are consistent with results of a meta-analysis of MSI-H tumors across several microarray datasets [ 33 ], as well as in MMR deficient CRC tumors [ 34 ]. CD8 + T tumor infiltrating lymphocytes (TIL)s were also seen in greater number in MSI-H tumors [ 35 ].…”
Section: Discussionsupporting
confidence: 86%
“…We first aimed to determine cell type composition differences between MSI-H and MSS/MSI-L CRC tumors. We replicated a number of known findings, including increased CD8 + T cells and macrophages in MSI-H tumors, which are consistent with results of a meta-analysis of MSI-H tumors across several microarray datasets [ 33 ], as well as in MMR deficient CRC tumors [ 34 ]. CD8 + T tumor infiltrating lymphocytes (TIL)s were also seen in greater number in MSI-H tumors [ 35 ].…”
Section: Discussionsupporting
confidence: 86%
“…The PPI results showed that MSH6 was highly correlated with CXCR6, IDO1, TNFRSF9, FCGR3B, IL13, KLRK1, CXCL10, CD27, CD19, IFNG, FOXP3 and CD8A. Walter Rayford et al showed that IFNG has a negative correlation with MSH6 in prostate cancer 27 . Hee Sang Hwang et al showed that CD8-and FoxP3-positive colorectal and gastric cancers were more strongly correlated with microsatellite instability (MSI) 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin blocks fixed with 8% formaldehyde containing sufficient tumor for analysis were prepared for hematoxylin and eosin (HE) staining and tissue microarray (TMA) analysis by extracting a core with a diameter of 3 mm from each case. Additionally, the TMA was subjected to immunostaining using antibodies against the following mismatch repair proteins (MMRPs): MLH1 (ES05; mouse monoclonal; dilution 1:50), PMS2 (EP51; rabbit monoclonal; dilution 1:40), MSH2 (FE11; mouse monoclonal; dilution 1:50), or MSH6 (EP49; rabbit monoclonal; dilution 1:50; Agilent Technologies, Santa Clara, CA, USA), as described previously [ 10 ]. Representative images of the slides were captured with an Olympus DP74 camera (lens, × 40; Olympus, Tokyo, Japan) using the CellSens Standard software (Olympus, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…LGR5 mRNA detection was performed using the RNAscope® kit (Advanced Cell Diagnostics, Hayward, CA, USA), as described previously [ 10 ]. Additionally, a four-step evaluation method we reported previously was used [ 10 ]. Furthermore, LGR5 mRNA expression levels were categorized as low expression (grades 0, 1+, 2+, and 3+) and high expression (4+).…”
Section: Methodsmentioning
confidence: 99%